Revolutionary, Permanent Tensioned Membrane Aluminum Frame Supported Structures. - Novak, Celeste Allen (Architectural Record, 2023)
Describe the architect's role in managing the installation of rapidly constructed tensioned membrane aluminum frame supported structures. Design and technological advances in tensioned membrane aluminum frame supported structures may provide an alternative for owners and architects who want it all.